Cisto dentígero: estudo epidemiológico, correlação clinicopatológica e caracterização de uma possível variante inflamatória - Godoy, Gustavo Pina (2006)
The aim of this study was to evaluate the clinical and pathological features of cases diagnosed as dentigerous cyst by the Department of Oral Pathology, School of Dentristy at the Federal University of Rio grande do Norte, attempting the possible correlation between histomorphological findings and epidemiological data contained at the files of the patients, in order to define a suggested variation of lesion named inflammatory dentigerous cyst. It was verified that dentigerous cyst are more frequently present in the earfy three decades of life, with the majority of cases occuring in the second decade (40,740/0 ), and also male (57,41%) and white patients (68,52%) were most affected. In relation to anatomic site, the dentigerous cyst was more prevalent at anterior maxila and posterior mandible, showing, usually, a slow growth pattem. The majority of lesions were asymptomatic and the radiographic observed was frequently na unilocular radiolucency. In regard to the histomorphological analysis, it was noticed that the lesions showed commonly a thin epithelium, with a capsule of fibrous connective tissue, richly vascularized and collagenized with an intense mononuclear inflammatory infiltrate. Finally, clinicopathological was performed and it was find out that cysts that showed a thick epithelium, with a high degree of vascularization and collagenization, intense inflammatory infiltrate in the cystic capsule, were located in the pre-molares region, in patients under 12 years old and the majority showing painfull sintomatology, properly, compatible with inflammatory dentigerous cyst. The findings of the present study indicate that, probably, there is a variant of the dentigerous cyst, and therefore, we suggest the denomination inflammatory follicular cyst for this entity